2009
DOI: 10.1111/j.1467-9248.2009.00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Latin American Canadians Rethink Their Political Spaces: Grass-Roots or Electoral Participation?

Abstract: Framed by the debate on the decline of party politics and the rise of grass‐roots participation, this article explores the civic and political involvement of a group of Latin American immigrants in the city of Toronto. The data were drawn from 100 interviews and two focus groups, one composed of participants who, in Canada, participated at the grass‐roots level, and another focused on interviewees who were engaged in political parties. Overall results indicate that, compared to Latin America, in Canada there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…For migrants, electoral politics seems to be more elusive, because they find a series of obstacles that prevent them from participating to a significant extent (Montoya, 2002; Passel, 2004; Stasiulis and Abu‐Laban, 1991). Some works have analysed the differences between electoral and grassroots politics among migrant communities, suggesting that migrants participate more in the latter because bureaucratic barriers, mandatory language skills and discrimination tend to be less prevalent (Ginieniewicz, 2009; Long, 2002; Stasiulis, 1997).…”
Section: Contextual Backgroundmentioning
confidence: 99%
“…For migrants, electoral politics seems to be more elusive, because they find a series of obstacles that prevent them from participating to a significant extent (Montoya, 2002; Passel, 2004; Stasiulis and Abu‐Laban, 1991). Some works have analysed the differences between electoral and grassroots politics among migrant communities, suggesting that migrants participate more in the latter because bureaucratic barriers, mandatory language skills and discrimination tend to be less prevalent (Ginieniewicz, 2009; Long, 2002; Stasiulis, 1997).…”
Section: Contextual Backgroundmentioning
confidence: 99%
“…The context of exit and reception that organize a migration flow, including government and civil society reception as well as the networked resources of the national origin or ethnic group, have a significant effect on the character of immigrant organizations (Portes, Escobar, & Arana, 2008). Premigration political socialization and organizational dispositions are also important factors because they shape the ways of organizing to which different groups of immigrants are disposed by virtue of their experiences with politics and collective action before migration (Ginieniewicz, 2009; Moya, 2005; White, Nevitte, Blais, Gidengil, & Fournier, 2008). In our research, we find that the context of departure, specifically, variation in forms of political violence, and direct or indirect forms of exposure to organized and partisan politics have a significant impact on immigrant ways of organizing , including the kinds of organizations they create in Toronto and the forms of collective action or endeavors they are comfortable undertaking (Landolt & Goldring, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The few scholars who have studied Latin American political transnationalism in Canada found that although Latinxs in Ontario (i.e. Chilean, Salvadoran, Guatemalan, and Mayans) had an active political participation in homeland politics in the late 1970s and 1980s, their political participation in Canadian issues was low (Escobar 2000;Ginieniewicz 2010b;Landolt 2007b;Landolt and Goldring 2009;Nolin Hanlon 2000Veronis 2006a). This configuration was generated by Canada's somewhat welcoming context of refugee reception before the 1990s, which allow them to exert their pre-migration political socialization, activism, and agency in Canada (Landolt 2007b;Landolt and Goldring 2010;Peddie 2014;Snow 2013).…”
Section: Local (Trans)national and Global Political Engagementmentioning
confidence: 99%